Investigation of Static & Active Structural Colouration in Ultrathin Film Lossy Fabry-Perot Resonator Stack Structures - Roy, Evan (Trinity College Dublin. School of Physics. Discipline of Physics, 2025)
The main aim of the research laid out in this work is to characterise the optical response of high index lossy absorbers like MoS2, Si, Ge, VO2, and Nio in various all-thin-film Fabry-Perot wave interference nanocavity stack structures. More specifically I wish to ascertain how strong absorption, light-matter interaction, and colouration, can be explained in these multilayer assemblies when ultrathin lossy layers are used in conjunction with either opaque or semi-transparent back reflective metals like Ag, Au, Al, W, Cr, and Ni, which are sometimes also paired with lossless transparent dielectric spacers and anti-reflection coating films. An all-thin-film (ATF) approach in this context refers to a thin film device that requires no lithography in the manufacturing process, also known as a lithography-free process. By focusing on an ATF stack structure, many of the drawbacks that are traditionally associated with nanofabrication, such as increased design cost and complexity, can be circumvented. Thus, the research presented will focus mainly on using thin film interference as the primary strategy to create structural colour over other patterned metasurface methods. Simple two-layer stacks that access the normally forbidden zeroth order Fabry-Perot mode will be discussed at length for the lossy materials mentioned in both passive and active settings. Additionally, other phenomena like broadband near perfect absorption in the ultrathin regime will also be explored in the context of a lithography free approach, demonstrating how careful thin film design can concentrate most of the incoming light across the visible into extremely thin high index absorbing layers less than 10 nm in thickness. Furthermore, the same concept of focusing light into an ultrathin absorbing film will also be shown to produce steep and bright structural colour when coupled with a higher order Fabry-Perot mode associated with the narrower metal-insulator-metal (MIM) resonator, in a design known as a Fano-resonant cavity. Using this stack configuration, it will be evident that the performance of active index change devices, based on electrochromic and phase change active materials like NiO and VO2, are greatly enhanced in terms of their on/off state contrast in reflection. Moreover, it will be shown that the colour gamut and resonant peak brightness performance of these Fano-resonant devices supersedes the two-layer zeroth order Fabry-Perot mode stack structures.
APPROVED
Keywords: Fabry-Perot Resonance; Electrochromics; Thin Film Structural Colour; Ultrathin Lossy Dielectrics; Spectroscopic Ellipsometry; Optics; Magnetron Sputtering; Zeroth Order Fabry-Perot Mode; Transfer Matrix Method; 2D Nanomaterials